Ativismo de mulheres negras em Cuiabá : práticas de comunicação e vinculação social - Pinto, Neusa Baptista (2018)
This research investigates the communicational dimension of the mobilization and organization practices of black activist women in the city of Cuiabá (MT), based on the theoretical model of communication as culture (LIMA, 2001) and, within this, the understanding of communication as a social link (SODRÉ, 2014), which shifts the phenomenon from the scope of technointeraction and privileges the primary processes of communication, reaffirming it as part of human existence itself. Specific objectives are: a) to identify the meanings attributed by the subjects to the emerging patterns that characterize the generality and the singularity of black women's activism in Cuiabá, in the biennium 2016- 2017; c) evidence aspects of the relationship between activism, daily practices and subjectivity and d) observe the communicational dynamics of social practices mediated by the affirmation of blackness. The term communication (communicatio) has the same radical of community, common, communicate, etc., referring to sharing, proximity, "being with". Social bonding is the basis of the mode of organization of women observed for the present study, which is considered from the notion of rhizome (multiplicity) (Deleuze and Guattari, 1995), which shows its eminently heterogeneous, a-centered character and not hierarchical, considering what he presents not only what he denies. We approach the subjectivity of the black woman based on the notion of identity as rhizome, which portrays the unstable character of the hybrid subjectivities that emerge with the phenomenon of creolization (GLISSANT, 2013). The study is descriptive and had as a methodological proposal the participant research (BRANDÃO, STRECK, 2006) with seven black women from the Institute of Black Women of Mato Grosso (2002) and follow-up of two black women linked to the Hip Hop Women's Group (2015) and the Feminist Front of UFMT (2013). Events were observed (meetings, concerts, talk wheels, visit, lecture, party, protests), which are considered spaces of social connection. The group has different characteristics in relation to the current idea of activism or militancy that, in general, gives greater legitimacy to what comes close to the unity, fixity and homogeneity characteristic of the hegemonic organizational model. It is based on creativity: while acting, it also creates itself. The collaborative way in which the activities are carried out and the diverse way in which women "participate" in groups are characteristic of what we call the "rhizomorphic mode of organization." The virtue of social bonding among black women lies in the creating a community as a collectivity based on affectivities and affinities, in the "original symbolic obligation" (Sodré, 2014), in opposition to the model ofcorporate relationship. Besides demonstrating organizational limitation, it demonstrates the mobilizing potential of everyday practices.